Contribution of Sports Training to the Discipline of Indonesian Athletes with Special Needs - Permana, Dian; Tarigan, Beltasar; Budiana, Dian; Hendrayana, Yudy; Faridah, Ai; Budiman; Lardika, Rola Angga (Universitas Majalengka, 2024)
Sports provide physical benefits and help people with special needs to be disciplined in managing their time and being wise. This research aims to analyse the contribution of sports training in building the discipline of athletes with special needs in Indonesia. This research uses quantitative descriptive methods. A total of 47 athletes were the research samples, taken using purposive sampling techniques. The research instruments are a questionnaire sheet and Google form for the implementation of sports training, a questionnaire for the discipline of athletes with special needs, which have been tested for validity and reliability—data analysis using quantitative descriptive analysis, linear regression analysis and determination tests. The contribution of sports training in building the disciplined character of athletes with special needs is 45.6% in the moderate category; factors/variables outside the research cause other influences. Sports training contributes to building the disciplined character of athletes with special needs in Indonesia, with the amount of contribution being in the moderate category. Knowing the impact of sports training on the character of athletes with special needs in Indonesia shows that sport contributes to building discipline. This conclusion is helpful as it provides information and data for the progress of sports and is a basis for diagnosing the development of athlete character and personality, specifically regarding the disciplinary character of athletes with special needs in Indonesia.